Existence Of Ψ - Bounded Solutions for Lyapunov Systems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research paper, the researchers present an indispensable and adequate condition for the existence of Ψ-bounded solution for the linear non- homogeneous Lyapunov matrix differential system on R. Besides, it is given a result in connection with the asymptotic behaviour of the Ψ- bounded solutions of a linear non- homogeneous Lyapunov matrix differential equation.